Novel Deep Learning Techniques For Computer Vision and Structure Health Monitoring - Pathirage, Chathurdara Sri Nadith (Curtin University, 2018)
This thesis proposes novel techniques in building a generic framework for both the regression and classification tasks in vastly different applications domains such as computer vision and civil engineering. Many frameworks have been proposed and combined into a complex deep network design to provide a complete solution to a wide variety of problems. The experiment results demonstrate significant improvements of all the proposed techniques towards accuracy and efficiency.